2021
DOI: 10.1175/mwr-d-20-0267.1
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation Impact of Early FORMOSAT-7/COSMIC-2 GNSS Radio Occultation Data with Taiwan’s CWB Global Forecast System

Abstract: The FORMOSAT-7/COSMIC-2 Global Navigation Satellite System (GNSS) Radio Occultation (RO) satellite constellation was launched on June 2019 as a successor of the FORMOSAT-3/COSMIC mission. The Central Weather Bureau (CWB) of Taiwan has received FORMOSAT-7/COSMIC-2 GNSS RO data in real time from Taiwan Analysis Center for COSMIC. With the global numerical prediction system at CWB, a parallel semi-operational experiment assimilating the FORMOSAT-7/COSMIC-2 bending angle data with all other operational observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The Constellation Observing System for Meteorology, Ionosphere, and Climate mission II (COSMIC‐2; also known as the Formosa Satellite mission 7) that launched in June 2019 is the latest GNSS RO satellite system (Schreiner et al., 2020). The early results showed that COSMIC‐2 data benefited the global and regional forecasts and research (Cucurull & Casey, 2021; Lien et al., 2021; Singh et al., 2021). In this study, we test the hypothesis that assimilating GNSS RO data significantly improves the overall performance of TC formation forecasts, including false alarms, and explore the physical reasons behind such improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The Constellation Observing System for Meteorology, Ionosphere, and Climate mission II (COSMIC‐2; also known as the Formosa Satellite mission 7) that launched in June 2019 is the latest GNSS RO satellite system (Schreiner et al., 2020). The early results showed that COSMIC‐2 data benefited the global and regional forecasts and research (Cucurull & Casey, 2021; Lien et al., 2021; Singh et al., 2021). In this study, we test the hypothesis that assimilating GNSS RO data significantly improves the overall performance of TC formation forecasts, including false alarms, and explore the physical reasons behind such improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, Liu, et al ., 2021). A positive impact of assimilating the FS7‐C2 data on weather forecasts has been obtained in the Tropics in some preliminary studies (Lien et al ., 2021; S.‐Y. Chen, Nguyen, and Huang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Lien et al . (2021) also reported that the RO data under a few kilometers tend to be rejected due to the issues of larger data uncertainty and negative bias. Schreiner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Each receiver was integrated with four antennas, two for determining precise satellite orbit and other two to provide principal measurements of radio occultation. As a mainline task for numerical weather prediction and climatology, UCAR had processed the raw RO measurement data to retrieve neutral atmosphere parameter since October 1st, 2019, for which improved the reliability of global climate monitoring by unique RO properties (Healy S. 2020;Benjamin R et al 2021;Guo Y et al 2021).…”
Section: Introductionmentioning
confidence: 99%